Calcium-binding proteins and RAGE: from structural basics to clinical applications - Heizmann, Claus W. (Methods in molecular biology, 2013)
A major direction in medical research leading to clinical applications targets the regulation of intracellular calcium and the various human diseases associated with an altered homeostasis of this global second messenger. These diseases include, for example: cardiomyopathy, inflammation, brain disorders, diabetes and cancer. In Calcium Binding Proteins and RAGE: from Structural Basics to Clinical Applications, expert researchers in the field detail many of the methods which are now commonly used to study calcium binding proteins. These methods and techniques, such as calcium-measurements, screening methods, clinical chemistry, and therapy, are generally applicable to many other areas of basic and medical research as well as to diagnostics. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Calcium Binding Proteins and RAGE: from Structural Basics to Clinical Applications underlines the diagnostic and clinical importance of this family of proteins in human diseases and as drug targets.